Menentukan Koefisien Restitusi Tumbukan dengan Analisis Konversi Sudut Penyimpangan - M. Yasin Kholifudin (Jurnal Penelitian Pembelajaran Fisika, 2019)
Physical practicum-based learning on collision was been carried out with the aim of knowing the magnitude of the coefficient of restitution of collision of 2 toy balls that are hung on station with a rope by analyzing the conversion of angle of the deviation before and after collision to the magnitutde of  velocity. The instruments used in the practicum were“ tek-tek” balls, “ping-pong” balls, clear rubber ball, bow, stationary. Data collection was taken from the 8 practicum groups each of which  consists of 4 students in class X IPA 1 of Senior High School 2 Kebumen in the 2nd semester of the school year 2017/2018. Conclusions obtained from data analysis are the conversion of angle of deviation before and after collision to the magnitude of velocity, average collision coefficient; between “tek-ball” was  0.18, “tek-tek” ball with clear rubber ball was 0.26, “tek-tek” ball with “pingpong” ball was 0.64. So that the three collisions include a partially resilient collision which has a range of restitution coefficients 0 ˂ e ˂ 1.Students did the practicum carefully, students had fun learning while playing and collision. This practicum can be done as an alternative to teach the competency on KI-4